BASICS OF DIRECTING FOREIGN INVESTMENTS TO UZBEKISTAN (E Global Congress, 2024)
In this thesis, the factors of creative competence development in the investment field are explained in order to increase the competence of our students in the field of investment, to further develop their knowledge, to gain some experience. From this point of view, we want to touch on the investment sector.